Quality of service multicast routing protocol for large scale MANETs - Qabajeh, Mohammad M.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Qabajeh, Liana K. (2009)
—Mobile Ad hoc NETworks (MANETs) are collection of mobile nodes communicate in a multi-hop manner without relaying on any infrastructure or central administration. Multimedia and group-oriented applications over MANETs gain high popularity, which makes providing Quality of Services (QoS) a key requirement. This work proposed a new efficient approach which aims to find paths between the source and all the multicast group members using paths that meet the bandwidth and delay requirements. Unlike some of multicast routing protocols, the proposed approach has limited maintaining the network topology to certain nodes to reduce communication overhead and provide scalability. The proposed protocol partitioned the network into equal size hexagonal cells and a leader and backup leader are elected inside each cell. The location information provided by GPS receivers are used at route discovery and route maintenance. This protocol allows multicast group members to join/leave the held session dynamically. The proposed protocol is scalable for large area networks with large multicast members. Also, it achieves a significant reduction in processing overhead than non hierarchical algorithm